2010
DOI: 10.1016/j.soilbio.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Amounts of carbon mineralised and leached as DOC during decomposition of Norway spruce needles and fine roots

Abstract: a b s t r a c tChanges in climate or forest management practices leading to increased litter production will most likely cause increased leaching rates of dissolved organic carbon (DOC) from the O horizon. The rhizosphere is often assumed to have a large carbon flux associated with root turnover and exudation. However, little has been done to quantify the amount of DOC originating from root litter. We studied decomposition of fine root and needle litter of Norway spruce (Picea abies) through a combined incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 36 publications
10
43
0
Order By: Relevance
“…After all, C availability is usually considered to be the main limiting resource for soil microbial growth [6]. Fine root and floor litter have been found to be important sources of soil DOC [21]. Our field data showed that fine root biomass increased by 39% in the HP treatment compared to the control (Fig.…”
Section: Figmentioning
confidence: 64%
“…After all, C availability is usually considered to be the main limiting resource for soil microbial growth [6]. Fine root and floor litter have been found to be important sources of soil DOC [21]. Our field data showed that fine root biomass increased by 39% in the HP treatment compared to the control (Fig.…”
Section: Figmentioning
confidence: 64%
“…Data by Crow et al (2009) suggest that lignin concentrations of roots are in the range of those of leaf and needle litter. Root-derived DOM shows higher concentrations of aromatic compounds than DOM from foliar litter (Hansson et al, 2010;Uselman et al, 2012). Hansson et al (2010) showed that DOM production during root decomposition occurs in patterns that are similar to those of needle decomposition.…”
Section: Argument 3: Roots As a Source Of Stabilized Aromatic Sommentioning
confidence: 97%
“…Hence, losses of lignin-derived C during litter decomposition can occur due to leaching of water-soluble products of an incomplete degradation or as CO 2 . Laboratory incubation tests on water-extractable organic matter from various plant and soil materials suggest that aromatic components are more resistant to mineralization than non-aromatic components (Pinney et al, 2000;Kalbitz et al, 2003a, b;Marschner and Kalbitz, 2003;Don and Kalbitz, 2005;McDowell et al, 2006;Hagedorn and Machwitz, 2007;Fellman et al, 2008;Hansson et al, 2010;Kothawala et al, 2012;Toosi et al, 2012). This suggests that leaching is an important factor in loss of lignin-derived matter during litter decomposition.…”
Section: Argument 2: Preferential Stabilization Of Aromatic Dom Compomentioning
confidence: 99%
“…UV absorbance was then measured at 280 nm using a UV spectrophotometer. Finally, SUVA 280 was calculated as absorbance divided by WEOC concentration (Hansson et al, 2010) and is expressed as g of dry peat per mg C − 1 cm − 1 .…”
Section: Water-extractable Organic Matter Analysesmentioning
confidence: 99%